2017
DOI: 10.1111/apa.13770
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of film on preschool children's behaviour dependent on editing pace

Abstract: Aim: Evidence on how the pace of television and film editing affects children's behaviour and attention is inconclusive. We examined whether a fast-paced film affected how preschool-aged children interacted with toys. Methods:The study comprised 70 children (36 girls) aged 2-4.5 years who attended preschools in Essex, United Kingdom. The children were paired up and tested with either a fast-or a slow-paced film of a narrator reading a children's story. The fast-paced version had 102 camera cuts and 16 still im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
21
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 24 publications
6
21
1
Order By: Relevance
“…For 3-year-olds, viewing the fast-paced program led to slight negative effects on subsequent behavior in terms of attention and effort. This somewhat supports previous findings (Geist & Gibson, 2000;Kostyrka-Allchorne et al, 2017) that a faster-paced program negatively impacted sustained attention directly after viewing. Although these studies included children of a similar age to the current research (4-to 5-and 2.5-to 4-year-olds respectively) they were not designed to investigate age differences.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…For 3-year-olds, viewing the fast-paced program led to slight negative effects on subsequent behavior in terms of attention and effort. This somewhat supports previous findings (Geist & Gibson, 2000;Kostyrka-Allchorne et al, 2017) that a faster-paced program negatively impacted sustained attention directly after viewing. Although these studies included children of a similar age to the current research (4-to 5-and 2.5-to 4-year-olds respectively) they were not designed to investigate age differences.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, it seems that it is the occurrence of these fantastical events that may reduce EF rather than the pace of the program. Furthermore, it seems that depending on the EF skills being tested the pace of the program may have a facilitative effect, as found in this study and also by Cooper et al (2009) and Kostyrka-Allchorne et al (2017). Although Lillard et al (2015) found no effect of pace, their EF tasks predominantly required sustained attention and following of rules (e.g.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Three additional studies met the inclusion criteria and were included in this update. These comprised one RCT [ 31 ] and two longitudinal studies [ 32 , 33 ]. In the RCT, 70 preschoolers were randomized to watching a fast or slow-paced film to examine the subsequent effect on children’s attention.…”
Section: Resultsmentioning
confidence: 99%